Nomogram to predict periprosthetic joint infection after total hip arthroplasty using laboratory tests - Junzhe Lang; Zetao Dong; Boyuan Shi; Dongdong Wang; Jiandong Yuan; Lei Chen; Jianqing Gao; Anan Sun; Jiyue Huang; Zhiqiang Xue (Journal of Orthopaedics and Traumatology)
Abstract Background Periprosthetic joint infection (PJI) is a catastrophic complication after joint arthroplasty. This study aimed to analyze the relationship between laboratory tests and PJI and establish a nomogram for predicting risks of PJI after total hip arthroplasty (THA). Materials and methods The clinical data of patients who underwent THA from January 2015 to December 2020 were retrospectively analyzed. Demographic and relevant clinical information of patients was collected; independent risk factors associated with PJI were determined by univariate and multivariate logistic regression analysis, and receiver operating characteristics (ROC) were drawn to analyze the specificity and sensitivity of each risk factor. Risk factors are included in the nomogram. Calibration curve and decision curve analysis were used to evaluate the predictive accuracy and discriminability of the model. Results A total of 589 patients were enrolled in the study, of whom 87 were eventually diagnosed with PJI. Multivariate logistic regression analysis showed that serum C-reactive protein, erythrocyte sedimentation rate, polymorphonuclear neutrophils, D-dimer, and platelet count were independent risk factors for PJI after THA. The ROC curve analysis model of multivariate combined diagnosis had good diagnostic value, sensitivity was 77.01%, and specificity was 75.51%. The calibration curve shows good agreement between the prediction of the line graph and the actual observed results. The decision curve shows that the nomogram has a net clinical benefit. Conclusions The changes in serum C-reactive protein, erythrocyte sedimentation rate, polymorphonuclear neutrophils, D-dimer, and platelet count are related to the occurrence of PJI after hip arthroplasty. The nomogram prediction model established in this study is promising for the screening of PJI after hip arthroplasty. Level of evidence: Level III evidence. Non-randomized controlled cohort/follow-up study.